(untitled) (International Journal of Engineering and Computer Science, 2015)
In the recent years, despite of massive work made in protecting and securing the image using watermarking schemes, there still exists some flaws. One way to get rid of this is usage of well built reversible watermarking scheme as proposed. This work intends to make the process: reversible ,invisible and highly secure. De-Identification is a process which can be used to ensure privacy by concealing the identity of individuals captured. This additional de-identification process aids in achieving high security. One important challenge is to make the obfuscation process reversible so that the original image can be recovered by persons in possession of the right security credentials. This work presents a novel Reversible De-Identification method that can be used in conjunction with any obfuscation process, here the obfuscation process used is k-same obfuscation process . The residual information needed to reverse the obfuscation process is compressed, authenticated, encrypted and embedded within the obfuscated image using a two-level Reversible Watermarking scheme. The proposed method ensures an overall single-pass embedding capacity of 1.25 bpp, where 99.8% of the images considered required less than 0.8 bpp while none of them required more than 1.1 bpp. Experimental results further demonstrate that the proposed method managed to recover and authenticate all images considered.